2009
DOI: 10.1016/j.diabres.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the discussion and treatment of depressive symptoms accompanying type 2 diabetes

Abstract: Objective To compare rates of discussion and treatment for depression among African Americans and Whites with diabetes. Methods Measures of diabetes status, depressive symptoms, and history of discussing and being treated for depression were collected from 56 adults with depressive symptoms accompanying diabetes who were drawn from a larger study of type 2 diabetes. Results Analyses adjusted for confounders and multiple tests indicated that relative to Whites, African Americans were 6–12 times less likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…For example, past findings show that physicians are less likely to detect [67] and discuss depression [68] with Black American patients. Additionally, Black American patients may be less likely to disclose their symptoms to physicians [52]. Also, evidence shows that individuals treated by psychiatrists or psychologists are more likely to receive adequate depression treatment relative to those treated by primary care physicians [69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, past findings show that physicians are less likely to detect [67] and discuss depression [68] with Black American patients. Additionally, Black American patients may be less likely to disclose their symptoms to physicians [52]. Also, evidence shows that individuals treated by psychiatrists or psychologists are more likely to receive adequate depression treatment relative to those treated by primary care physicians [69].…”
Section: Discussionmentioning
confidence: 99%
“…Findings are mixed, with some reporting better treatment [4, 44-47], while others have reported worse treatment [14], or null effects [5]. The handful of studies that have investigated these relationships among Blacks report that Blacks with comorbid depression and T2DM are less likely to be diagnosed with [48, 49] and treated for depression [49-52]. One plausible explanation is that Blacks with comorbid T2DM and depression are unlikely to discuss their depression with their physicians, partly as a result medical mistrust, stigma, and cultural beliefs around responding to depression with stoicism [52].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Co-morbid depression also results in higher utilization for both medical and mental health care, and higher health care costs [15,17,18]. Furthermore, previous studies have shown that co-morbid depression may often be unrecognized and untreated in individuals with diabetes [1921]. With emerging evidence that depression treatment improves patient outcomes [2225], it is important to clarify which diabetes patients are at risk for depression, and the relationships between depression, quality of care and outcomes for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that persons diagnosed with T2D are at an increased risk of developing depression compared to persons without T2D (Nouwen et al, 2010;Penckofer, Doyle, Byrn, & Lustman, 2014) African Americans with T2D are often unlikely to discuss their depressive symptoms with their health care professionals, to be seen by a psychiatrist, or to be prescribed antidepressants (Wagner et al, 2009).…”
Section: Marital Statusmentioning
confidence: 99%